The Potential of Cyber Attacks in Indonesia's Digital Economy Transformation - Beny Abukhaer Tatara; Bisma Abdurachman; Desta Lesmana Mustofa; David Yacobus (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2023)
In the era of the industrial revolution 4.0, many activities use the internet and computers, including economic activities. Many activities in real space are transformed into cyberspace. Currently, the world economy is transforming from conventional methods to digital. Thus, almost all countries in the world are competing to adapt to these changes, one of which is Indonesia which, based on the McKinsey report, ranks first as the country with the fastest growth in adopting the digital economy. The purpose of writing this article is to analyze the potential for cyber attacks that can affect the transformation of Indonesia's digital economy. The research method used is qualitative with data collection techniques in the form of literature studies. The results of the study found that there are several potential cyber attacks in the transformation of Indonesia's digital economy, including: Denial-of-service (DoS) and distributed denial-of-service (DDoS) attacks, Man-in-the-middle (MitM) attacks, Phishing attacks, Drive-by-download attack, Password Attack, SQL Injection Attack, Cross-site scripting (XSS) attack, Eavesdropping attack, Birthday Attack, and Malware Attack. (Pada era revolusi industri 4.0, banyak aktivitas yang menggunakan internet dan komputer, termasuk aktivitas ekonomi. Banyak aktivitas di dunia nyata ditransformasikan ke dunia maya. Saat ini, perekonomian dunia sedang berubah dari metode konvensional ke digital. Oleh karena itu, hampir semua negara di dunia sedang bersaing untuk menyesuaikan diri dengan perubahan ini, salah satunya adalah Indonesia yang, berdasarkan laporan McKinsey, menduduki peringkat pertama sebagai negara dengan pertumbuhan tercepat dalam mengadopsi ekonomi digital. Tujuan penulisan artikel ini adalah untuk menganalisis potensi serangan cyber yang dapat mempengaruhi transformasi ekonomi digital Indonesia. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data berupa studi pustaka. Hasil penelitian menemukan bahwa ada beberapa potensi serangan cyber dalam transformasi ekonomi digital Indonesia, di antaranya: Serangan Denial-of-service (DoS) dan distributed denial-of-service (DDoS), Serangan Man-in-the-middle (MitM), Serangan Phishing, Serangan Drive-by-download, Serangan Password, Serangan SQL Injection, Serangan Cross-site scripting (XSS), Serangan Eavesdropping, Serangan Birthday, dan Serangan Malware.)